2009
DOI: 10.1890/08-1804.1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of position, litter type, and water pulses on decomposition of grasses from the semiarid Patagonian steppe

Abstract: Litter lignin and nutrient content, annual rainfall, and biotic activity are not good predictors of litter decomposition in arid and semiarid ecosystems, suggesting that other factors may be important in controlling carbon turnover. We explored the relative importance of litter position (above- vs. belowground), litter type (leaf vs. root), and pulsed water events (large vs. small) on mass loss with grass species of the semiarid Patagonian steppe. In a factorial experiment of mesocosms, we incubated leaf and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 47 publications
7
68
0
Order By: Relevance
“…As expected, the decomposition rate increased by 22.2 % in buried litter compared with surface litter. This result is consistent with most previous studies Santos et al 1984;Moorhead and Reynolds 1993;Vivanco and Austin 2006;Austin et al 2009). Generally, the buried leaf litter is exposed to a relatively cool, moist microclimate based on either our available data (Figs.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…As expected, the decomposition rate increased by 22.2 % in buried litter compared with surface litter. This result is consistent with most previous studies Santos et al 1984;Moorhead and Reynolds 1993;Vivanco and Austin 2006;Austin et al 2009). Generally, the buried leaf litter is exposed to a relatively cool, moist microclimate based on either our available data (Figs.…”
Section: Discussionsupporting
confidence: 94%
“…Overall, significantly greater mass loss has been reported in buried litter than in surface litter in diverse ecosystems, especially in dry regions Santos et al 1984;Moorhead and Reynolds 1993;Vivanco and Austin 2006;Austin et al 2009). This may be due to favorable temperature and moisture regimes (compared to strong microclimate fluctuations on or above the surface; see above), which benefit microbial activity in buried litter (Elkins and Whitford 1982;Moorhead and Reynolds 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These correlations are much less obvious in low rainfall ecosystems, where standard indicators of litter chemistry do not predict decomposition rates and nutrient release (14)(15)(16)(17). Recent experimental evidence has shown that, in semiarid ecosystems, abiotic photodegradation can be a dominant control on decomposition of decaying plant material (18).…”
mentioning
confidence: 99%
“…The difference between aboveground and belowground decomposition have been documented in other grassland systems, where a substantial difference in the magnitude of litter quality effect on decomposition was observed between leaf and root litter (Gholz et al 2000;Austin 2006, 2008;Austin et al 2009). Slow decomposition of root materials is thought to explain the greater contribution of belowground biomass than of aboveground biomass to the soil organic C pool (Johnson et al 2007).…”
Section: Discussionmentioning
confidence: 86%